Low EVI1 expression at diagnosis predicted poor outcomes in pediatric Ph-negative B cell precursor acute lymphoblastic leukemia patients. (17th February 2022) - Yang, Lu; Dao, Feng-Ting; Lu, Ai-Dong; Chen, Wen-Min; Li, Ling-Di; Long, Ling-Yu; Liu, Yan-Rong; Liu, Kai-Yan; Zhang, Le-Ping; Qin, Ya-Zhen
Abstract: Abnormally high ecotropic viral integration site 1 (EVI1) expression has been recognized as a poor prognostic factor in acute myeloid leukemia patients. However, its prognostic impact in B cell precursor acute lymphoblastic leukemia (BCP-ALL) remains unknown. A total of 176 pediatric Ph-negative BCP-ALL patients who received at least 1 course of chemotherapy and received chemotherapy only during follow-up were retrospectively tested for EVI1 transcript levels by real-time quantitative PCR at diagnosis, and survival analysis was performed. Clinical and EVI1 expression data of 129 pediatric BCP-ALL patients were downloaded from therapeutically applicable research to generate effective treatments (TARGET) database for validation. In our cohort, the median EVI1 transcript level was 0.33% (range, 0.0068–136.2%), and 0.10% was determined to be the optimal cutoff value for patient grouping by receiver operating characteristic curve analysis. Low EVI1 expression (<0.10%) was significantly related to lower 5-year relapse-free survival (RFS) and overall survival (OS) rates ( P = 0.017 and 0.018, respectively). Multivariate analysis showed that EVI1 expression <0.10% was an independent adverse prognostic factor for RFS and OS. TARGET data showed that low EVI1 expression tended to be related to a lower 5-year OS rate ( P = 0.066). In conclusion, low EVI1 expression at diagnosis could predict poor outcomes in pediatric Ph-negative BCP-ALL patients receiving chemotherapy. Supplemental data for this article is available online at https://doi.org/10.1080/08880018.2021.1939818 .